Urokinase-Induced Fibrinolysis of 125I-Fibrin - Ball, Anne P.; Day, Eugene D. (Thrombosis and Haemostasis, 1970)
By means of the density-gradient separation of soluble fibrin split products from 125I-labeled fibrin in 0.8-ml gradients, a micro-technique for the measurement of urokinase activation of plasminogen was developed. The conditions necessary to maintain first-order activation kinetics were obtained and incorporated into the micro-technique, thus providing a linear micro-assay of 0.1-ml volumes of urokinase in the range of 2.5-50.0 CTA units.